"Back to Basics" Approach for Improving Maternal Health Care Services Utilization in Lao PDR. (April 2016) - Ngan, Do Kim; Kang, Minah; Lee, Chaeun; Vanphanom, Sychareun
Earlier studies claim inadequate knowledge and understanding of maternal health care service among women and families account for low demand and utilization of these services. This study explores maternal service utilization in Lao PDR by interviewing women, families, health service providers, and community members in Xiengkhuang province. In general, women's attitude and acceptance of maternal health care were positive, with many expressing appreciation and need for maternal health services. Nevertheless, utilization of maternal health services remained poor largely due to dissatisfaction with services: inaccessibility, irregular services, fund shortage, poor facilities, and problems dealing with male health service providers. It appears that utilization of maternal health care services in Lao PDR is as much a health system concern as it is a user preference issue. This article advocates a "back to basics" approach for reviewing maternal health care infrastructure systems in developing countries to improve community health services and utilization.